Nirvana - Salvatores, Gabriele 1950-; Petriccione, Italo; Lambert, Christopher 1957-; Abatantuono, Diego 1955-; Rubini, Sergio 1959-; Rocca, Stefania 1971- (epix media AG, 2010)
Jimi, a computer game designer, discovers his latest product has been infected by a virus which has given consciousness to the main character, Solo. Begged by Solo to end its useless 'life', Jimi searches for help to delete the game before it's released
Original: Frankreich, Italien, Großbritannien 1997
Keywords: Video game characters / Drama; Video games / Drama; Video game characters; Video games; Drama; Feature films; Video recordings for the hearing impaired; Science fiction; Italian films; Film; DVD-Video